'Because she was born here': how children with citizenship rights affect precarious status migrant worker experiences in Canada. (23rd March 2022) - Foster, Jason
Canada is one of the few nations which grant citizenship to anyone born within its borders, a policy known as birthright citizenship. This policy creates the possibility that migrant workers with precarious residency status can be parents of children who hold claim to Canadian citizenship. This article examines the effect that citizen children have on the lived experiences of migrant workers by comparing two groups of migrant workers with precarious status in Canada: those who have children with citizenship rights and those who do not. It finds workers with citizen children have more precarious employment patterns, interact more with government agencies due to greater need to access services, possess different reasons for staying post-permit expiry, and are at greater risk of deportation.